2000
DOI: 10.1097/00004872-200018120-00015
|View full text |Cite
|
Sign up to set email alerts
|

ETA receptor blockade induces fibrosis of the clipped kidney in two-kidney-one-clip renovascular hypertensive rats

Abstract: The present study indicates that long-term blockade of the activated endothelin system in the clipped kidney of rats with renovascular hypertension using an ETA receptor antagonist led to a fibrotic atrophy of the clipped kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Ischemia on its own is a well-known pro-fibrotic stimulus (for review, see reference 33). A very recent study also demonstrates that long-term treatment with an ETA receptor antagonist in rats with two kidney-one clip (2K-1C) renovascular hypertension increases fibrosis in the clipped (ischemic) kidney (15).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Ischemia on its own is a well-known pro-fibrotic stimulus (for review, see reference 33). A very recent study also demonstrates that long-term treatment with an ETA receptor antagonist in rats with two kidney-one clip (2K-1C) renovascular hypertension increases fibrosis in the clipped (ischemic) kidney (15).…”
Section: Discussionmentioning
confidence: 94%
“…For pathohistologic evaluation, all samples were embedded in paraffin, cut in 3-m sections, and submitted to hematoxylin-eosin, Sirius red, and periodic acid-Schiff (PAS) staining and analyzed as recently described (15). The severity of interstitial matrix deposition was evaluated after Sirius red staining using a computer-aided imageanalyzing system.…”
Section: Histologic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, Hocher et al [23] found that in long-term renovascular hypertension in WKY rats, ET A receptor blockade with another compound (BQ-123) completely normalized the hypertrophy of intracardiac arteries compared to untreated 1C-2K, whereas ET B receptor blockade reduced cardiac fibrosis of the left ventricle to baseline values. In another experiment with 1C-2K renovascular hypertensive rats, the same group showed that long-term treatment with the ET A -RB BQ-123 led to a fibrotic atrophy of the clipped kidney characterized by a significantly reduced weight of the clipped kidney compared to the clipped kidney of the placebo-treated group and to a markedly enhanced interstitial fibrosis of these kidneys after long-term ET A blockade [24].…”
Section: Discussionmentioning
confidence: 96%
“…The essential role of ET B receptors in pathological fibrosis is shown by the observation that an ET B selective receptor antagonist, in contrast to an ET A selective receptor antagonist, prevented the development of cardiac fibrosis in hypertensive rats [Hocher et al, 1999]. ET A selective receptor antagonists actually may enhance renal or cardiac fibrosis [Hocher et al, 2000;Seccia et al, 2003], suggesting that selective ET A antagonism, by causing chronic stimulation of unantagonized ET B receptors, may be detrimental.…”
Section: Cell Proliferation and Fibrosismentioning
confidence: 99%